Atelectasis predicts poor prognosis in pediatric macrolides-unresponsive Mycoplasma pneumoniae pneumonia with A2063/2064G mutations treated with azithromycin - Cheng, Jie; Liu, Ya; Zhang, Guangli; Li, Yuanyuan; Tian, Xiaoyin; Tan, Liping; Luo, Zhengxiu (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveWe aimed to investigate prognostic indicators for pediatric macrolides-unresponsive Mycoplasma pneumoniae pneumonia (MUMPP) cases with A2063/2064G mutations with azithromycin therapy.MethodsThis was a retrospective observational cohort study conducted at the Children’s Hospital of Chongqing Medical University. Children with macrolide-resistant mutations (A2063/2064G) diagnosed as MUMPP who received only anti-Mycoplasma pneumoniae (MP) treatment with azithromycin were retrospectively enrolled. Logistic regression analysis was used to identify potential risk factors for predicting short-term (refractory Mycoplasma pneumoniae pneumonia [RMPP]) and long-term (bronchiolitis obliterans [BO] or bronchiectasis) adverse prognosis. The results were visualized using forest plots.ResultsThis study retrospectively included 82 children with MUMPP, and all received only azithromycin for anti-MP treatment. The incidence of pulmonary consolidation, pleural effusion, and atelectasis was 80.49% (66/82), 34.15% (28/82), and 24.39% (20/82), respectively. 29.27% (24/82) of patients diagnosed with RMPP, and 14.63% (12/82) of patients diagnosed with bronchiolitis obliterans (BO) or bronchiectasis diagnosed within one year after discharge. Logistic analysis showed that atelectasis was independently associated with short-term (RMPP) and long-term (BO or bronchiectasis) adverse prognosis (odds ratio [OR] 4.02, 95% confidence interval [CI] 1.03-16.00, P = 0.043; OR 5.62, 95% CI 1.04-32.80, P = 0.045; respectively).ConclusionAtelectasis predicts a poor prognosis for children with A2063/2064G MUMPP. The occurrence of atelectasis may indicate an increased risk of failure of current azithromycin treatment. Combined with the results of drug-resistant mutations, it is recommended to strengthen disease monitoring and individualized intervention evaluation.